Stereoretentive formylation of (S)-proline: new application of the self-regeneration of stereo-centres (SRS) principle via chelation to cobalt(iii). Issue 42 (6th October 2015) - Temizsoy, Mehmet; Sethi, Waqas; Reinholdt, Anders; Schau-Magnussen, Magnus; Bendix, Jesper; Hammershøi, Anders
Abstract : Vilsmeier–Haack-type formylation of ligated ( S )-prolinate was achieved stereoselectively at the substitution-inert cobalt(iii ) centre. While coordinated, the stereogenic N centre of the ( S )-prolinate ligand maintains chirality during reaction. Abstract : In a Vilsmeier–Haack-type formylation reaction the α-(dihydroxymethyl)-( S )-prolinato complex (+)578 - p -[Co(tren)( R C, S N )-Pro[CH(OH)2 ]O]Cl2 ·2H2 O (22 ) was produced stereoselectively (85% ee) from the ( S )-prolinato complex, (+)578 - p -[Co(tren)( S C, S N )-ProO]2 (H3 O)2 (HOEt2 )(O3 SCF3 )7 (18 ). Similar reaction of the ( S )-alaninato complex, (−)578 - p -[Co(tren)( S -AlaO)](H3 O)(O3 SCF3 )3 (13 ), produced the racemate, rac-p -[Co(tren)(AlaCH(OH)2 O)]SO4 ·2H2 O (17 ). The contrasting stereochemical outcomes of the formylation reaction with18 versus 13 were ascribed to the stereogenic character of the coordinated sec. amine of the ( S )-prolinate chelate in18, which serves to uphold a chiral environment during reaction, whereas reaction intermediates derived from13 lack this stereochemical feature. The stereoselective formylation of ( S )-proline, relying on coordination to an inert metal centre, as conducted here, constitutes a novel application of the concept of Self-Regeneration of Stereocentres (SRS). The α-(hydroxymethyl)-( S )-prolinato complex, (+)578 - p -[Co(tren)( R C, S N )-Pro(CH2 OH)O]Cl2 ·2H2 O (23 ) resulted from borohydride reduction of22 . The molecular structures of (+)578 - p -[Co(tren)( R C, S N )-Pro[CH(OH)2 ]O]Cl2 ·2H2 O (22 ), rac-p -[Co(tren)-(AlaCH(OH)2 O)]I2 ·H2 O (17 ) and (+)578 - p -[Co(tren)( R C, S N )-Pro(CH2 OH)O]Cl2 ·2H2 O (23 ) were established by X-ray crystallography.